A MODELAGEM MATEMÁTICA NA EDUCAÇÃO MATEMÁTICA COMO EIXO METODOLÓGICO DA PRÁTICA DO PROFESSOR DE MATEMÁTICA - Ferreira, Carlos Roberto (2016)
The Mathematical Modeling has experienced great advances in theoretical and practical discussions in academic circles in recent decades (BIEMBENGUT, 2009). However, what is observed is that the progress made timidly reach the classrooms and in a timely manner on some initiatives. We are convinced that specific activities are not sufficient for understanding the modeling and to be present in the practice of teacher. In the scope of this problem, we observed that investigate the practice of teacher who conducts modeling activities for a long time constituted the main core of our concerns, which prompted us to ask: What shows the practice of mathematics teachers of Basic Education when predominantly adopt the Mathematical Modeling as a methodological axis assumed a perspective of mathematics education? And with the answers, we aim "Understanding and theorizing about the practice of mathematics teacher, when adopting the mathematical modeling as the main methodological axis in mathematics education perspective." The theoretical framework is based on the most current views on mathematics education and the teaching of mathematics, which are present in the work of Fiorentini and Lorenzato (2006) and Rius (1989). As for the mathematical modeling of concepts, we sought to dialogue with other authors, however, we assume the design proposed by Burak (2004). Regarding the training of mathematics teachers in modeling, we focus on the reflective method and autonomy based on the work of Schön (2000), Freire (2001), Garcia (1999), Martins (2002) and Gatti (2008). Other theoretical elements and distinct authors were included in the discussions, as proved necessary inroads to understanding the constructed categories. The theoretical framework is articulated to the epistemology of Fleck (1986), which may elucidate the modes of thinking and acting teacher. The approach was qualitative, with interpretative paradigm and inductive method, and the researcher took the participant observation posture. The subjects are three teachers of Basic Education of Paraná. For data collection and analysis, we use a mixed approach between Grounded Theory and Ethnography, with the help of ATLAS.ti software that assisted in the organization of analytical data, specifically the diary of teachers and direct the researcher comments. The free categorization, axial and selective enabled the creation of eleven categories linked to a central category. The data shows that when the teacher adopts modeling as a methodological axis for a long period of time, this does not guarantee that it will adopt permanently Modeling in their practice, but experience has shown significant changes in their thinking style and its practice. Willingness to change was the central category found that strongly connects to other categories and demonstrated reduction of insecurity of teachers, greater job satisfaction, increased motivation, understanding the importance of planning before and during the modeling activities, progress in understanding on evaluation, attention to student behavior, evolution regarding their autonomy and recognition of the importance of constant reflection of their practice.